Inhibiting METTLl3-ATG5 axis-mediated harmful autophagy in macrophages could help reduce airway epithelial inflammation and remodeling in COPD - Chen Guiyang; Xia Zhiwei; Zeng Xianyou; Liu Hanying (Archives of Biological Sciences)
Cigarette smoke exposure leads to chronic obstructive pulmonary disease (COPD). We investigated the role and underlying mechanisms of methyltransferase-like 3 (METTL3) and autophagy-related protein 5 (ATG5) in the progression of COPD. In a COPD mouse model exposed to cigarette smoke, lung tissues showed increased levels of METTL3, p-p65/ p65, autophagy markers (LC3 and ATG5), inflammatory factors (interleukin-6, IL-8, and TNF-α), and airway remodeling markers (N-cadherin, α-SMA, and Tn-C), while p62 and E-cadherin levels were decreased. Expression of METTL3 and ATG5 was positively correlated. These findings are consistent with observations in RAW264.7 mouse mononuclear macrophages exposed to cigarette smoke extract (CSE). CSE inhibited cell viability while promoting autophagy. METTL3 knockdown counteracted CSE effects, and ATG5 overexpression reversed METTL3 knockdown outcomes. Methylated RNA immunoprecipitation-qPCR showed that METTL3 knockdown reduced m6A, and the actinomycin D assay suggested that METTL3 knockdown reduced ATG5 mRNA levels and lowered ATG5 mRNA stability. METTL3-knockdown RAW264.7 reduced the inflammation and airway remodeling markers in the co-cultured mouse bronchial epithelial cells. In conclusion, inhibition of the METTL3-ATG5 axis-mediated macrophage detrimental autophagy in COPD could alleviate bronchial epithelial cell inflammation and reduce airway remodeling.